Bankruptcy as Implicit Health Insurance - Mahoney, Neale (American Economic Review, 2015)
This paper examines the implicit health insurance that households receive from the ability to declare bankruptcy. Exploiting multiple sources of variation in asset exemption law, I show that uninsured households with a greater financial cost of bankruptcy make higher out-of-pocket medical payments, conditional on the amount of care received. In turn, I find that households with greater wealth at risk are more likely to hold health insurance. The implicit insurance from bankruptcy distorts the insurance coverage decision. Using a microsimulation model, I calculate that the optimal Pigovian penalties are three-quarters as large as the average penalties under the Affordable Care Act.